Source Credibility Beauty Vlogger, Parasocial Relationship Dan Customer Equity Viewers Youtube - Nadiya Fikriyatuz Zakiyah; Sri Hartini (Jurnal Manajemen dan Kearifan Lokal Indonesia, 2020)
This study discusses how social media like YouTube can foster parasocial relationships between beauty vloggers and YouTube viewers. Parasocial relationships are built on a clear communication process between celebrity and viewers credible source consisting of attractiveness, expertise and trust. In addition, parasocial relationships are considered important to grow customer equity. The research analysis technique using Partial Least Square (PLS) is a powerful analytical method because it is applied at all data scales, does not require much consideration, and the sample size does not have to be large. The number of respondents consisted of 180 respondents. The sampling technique in this study is purposive sampling, which is a sampling technique that is done intentionally and in accordance with all the required sample requirements. Criteria for respondents are those who value beauty vlogger Tasya Farasya and respondents who use YouTube . The results of the study showed that the attractiveness and trust variables towards parasocial relationships. Parasocial variables affect the relationship to the value of equity, brand equity and relationship equity.